HUBUNGAN STATUS GIZI DAN AKTIVITAS FISIK TERHADAP KADAR GULA DARAH PADA REMAJA - Lily Marleni; Mardiah; Dessy Suswitha; Zuhana; Lenny Astuti (LPPM STIKes Mitra Adiguna, 2026)
Currently, non-communicable diseases (NCDs) are not only suffered by the elderly, but are also increasingly being found in young and productive age groups, including children and adolescents. The number of NCDs in children is just as worrying as in adults. High blood sugar levels during adolescence increase the risk of diabetes in the future. Diabetes is characterized by high blood sugar levels. Blood sugar levels vary from person to person and are influenced by several factors such as age, gender, genetics, food intake, medication, stress, lifestyle, and physical activity. Furthermore, nutritional status also contributes to blood sugar levels. Nutritional status can be determined through body mass index (BMI). The purpose of this study was to determine the relationship between nutritional status and physical activity on blood sugar levels in adolescents. The approach used in this study was a cross-sectional approach. The cross-sectional approach is a type of research that emphasizes measuring independent and dependent variables only once. The sample size was 32 individuals. From the results of statistical tests, it was found that there was a relationship between nutritional status and blood sugar levels with a p value of 0.0296 and there was no relationship between physical activity and blood sugar levels with a p value = 0.478. It is hoped that future researchers will be able to conduct further research on non-communicable diseases using different methods and a wider number of samples